Rind color change and granulation in pummelo [Citrus maxima (Burm. Ex Rumph.) Merr.] fruit as influenced by 1-methylcyclopropene - Bayogan, E. V. (2023)
The rind color, granulation, and some physico-chemical characteristics of ‘Magallanes’ pummelo [Citrus maxima (Burm. ex Rumph.) Merr.] fruit treated with 1-methylcyclopropene (1-MCP) for 8 hours at 0, 50 or 500 nL•L-1 then stored at ambient conditions (26.39±0.66ºC,83.31±4.03% RH) for 12 weeks were evaluated. Peel color became more yellow as L*, a*, b*and hue values gradually increased during storage. Chroma slightly increased. Juice content, and electrolyte leakage did not vary among treatments. However, weight loss, visual quality, shriveling, decay, pH, total soluble solids (TSS), titratable acidity (TA) and TSS:TA were affected by 1-MCP. Compared to the control, weight loss in treated fruit was lower at 6 weeks after treatment (WAT) with better visual quality at 6 and 9 WAT because of lesser shriveling. At 12 WAT, fruit treated with 500 nL•L-1 exhibited the highest TA and lowest TSS:TA ratio. Granulation or vesicle drying was most frequently observed initially in the middle and stylarend sections of the fruit segment. Granulated samples exhibited higher pH and lower TSS than the non-granulated segments. Application of 1-MCP at 50 and 500 nL•L-1 did not influence the yellowing and granulation of ‘Magallanes’ pummelo fruit but it maintained good fruit visual quality for three weeks longer than untreated fruit.